Peran Artificial Intelligence dalam Personalisasi Strategi Pemasaran Digital - Nabilah Fikriyah; Theodorus Sendjaja (BADAN PENERBIT STIEPARI PRESS, 2025)
Digital marketing has grown rapidly in recent years; however, one of the greatest challenges today is capturing consumer attention amid an overwhelming flow of information. This study aims to analyze the role of Artificial Intelligence (AI) in personalizing digital marketing strategies to make them more effective and targeted. The research method used is a literature review, examining various scientific journals, books, and recent industry reports relevant to this topic. The findings reveal that the application of AI enables a much deeper and more efficient level of personalization compared to traditional market segmentation approaches. AI technologies such as machine learning, natural language processing (NLP), and predictive analytics allow companies to analyze massive amounts of consumer data in real-time. This capability helps businesses understand consumer preferences, behaviors, and interaction histories, enabling them to deliver highly relevant product recommendations, content, and advertisements to the right individuals, at the right time, through the most effective channels. The key findings of this study emphasize that integrating AI into digital marketing strategies significantly improves campaign effectiveness, enhances customer experience, and strengthens brand loyalty, ultimately leading to higher conversion rates. The implications indicate that implementing AI in digital marketing is no longer an option but a strategic necessity for businesses to remain competitive in today’s dynamic digital era. Therefore, AI can be considered a critical tool for creating personalized, interactive, and consumer-oriented marketing strategies that drive engagement and long-term business growth.